004 Partnering to Transform Clinical Research Into Evidence-Based Health Care Guidelines. (15th August 2013) - Wasson, N; Chang, C; Smith, MEB; Qaseem, A; Starkey, M; Buckley, D; Chou, R; Saha, S
Abstract : Background: A guideline-making body nominated pressure ulcer risk assessment, prevention, and treatment as evidence review topics to support the development of clinical practice guidelines, partnering with a funding agency and a systematic review team to conduct the research. Context: Collaboration may enhance evidence-based health care given that multiple organisations bring diverse resources and expertise to the process of guideline development. By partnering to develop systematic reviews (SR) with focused research questions, funders, review teams, and guideline committees can effectively evaluate and synthesise the voluminous evidence required to inform guidelines. Description of Best Practice: We describe our processes for linking reviews to guideline development, including: Nomination/refinement of focused review topics Clearly defined roles for each participant Development of comprehensive SRs Well defined processes to preserve the scientific integrity of the review while allowing for input from stakeholders Stakeholder and funder participation throughout the review process Development of the guideline Publication of the research results and guidelines. Lessons for Guideline Developers, Adaptors, Implementers, and/or Users: Challenges include balancing the interests of the nominator/guideline developer and a broader stakeholder audience; answering the clinically important questions needed to develop a guideline; effectively presenting the findings; and coordinating among groups. Collaboration ensures that SRs are focused and relevant to guideline committees, aiding in the development of research that meaningfully informs clinical guidelines. Synergy between partner organisations can lead to wider dissemination of findings and facilitate timely guideline development for implementing best practices to improve health outcomes.